Politik Dinasti Dalam Perspektif Administrasi (Studi Isu Politik Dinasti Menjelang Pemilihan Umum 2024) - tey seran, silverius; Risyah, Verlyana (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2024)
This research aims to analyze dynastic politics before the 2024 general election in Indonesia from the perspective of administration, Old Public Administration, and New Public Service. This research is motivated by the alleged controversy in the decision of Constitutional Court Number 90 / PUU-XXI / 2023 concerning providing additional experience in office from the election in the minimum age requirement for presidential / vice presidential candidates. By using Qualitative Research Methods with Narrative Analysis with a focus on narrative analysis, a significant difference was found between dynastic politics and the administrative paradigm. The administrative perspective tends to emphasize efficiency, professionalism, meritocracy, and public services oriented to the needs of the community in contrast to the tendency of bureaucratic practices in dynastic politics whose control system tends to favor certain groups under the control of a minority of elites.